"You can't hide your children anywhere": Perceptions of organizational support for work‐life during the pandemic among academic couples who parent. Issue 199 (17th October 2022) - Culpepper, Dawn K.; Blake, Daniel J.
Abstract: The COVID‐19 pandemic has refocused higher education on issues of work‐life conflict among faculty members with children. This study draws from interviews with 13 heterosexual couples (26 participants) who were employed as faculty members and who cared for at least one child during the pandemic. Using the theory of perceived organizational support, we considered how institutional actions shaped the extent to which academic couples who parent felt supported in managing pandemic‐related work‐life conflict. We found centralized mechanisms for sharing concerns, innovative childcare resources, and flexibility and transparent communication enhanced participants' sense of organizational support, while inaction and unsystematic institutional responses undermined perceptions of organizational support. Our findings are consistent with past work on the relationship between organizational policies and resources and perceptions of organizational support, but also suggest alternative strategies for institutions that want to enhance perceived and real support for academic couples who parent.